2020
DOI: 10.3390/su12093840
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Façade Color and Cost to Improve Visual Integration of Buildings in the Rural Environment

Abstract: In recent decades, rural buildings have proliferated in the rural environment, in many cases clashing with the surroundings. One of the main objectives in rural areas must be to maintain a balance between economic and sustainable development. In the exterior design of buildings, it is necessary to follow technical and scientific criteria that respect the natural environment, and one of the most important parameters in this scenario is façade color. This article analyzes the costs of using different colors on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…This may have an impact on color preferences as individuals develop their color preferences related to the appearances of spaces that they are accustomed to. The color preferences themselves do not suffice to predict the actual behavior of occupants vis-à-vis interior design colors; however, scholars include various demographic variables into the equation such as age, gender and ethnicity (Sable and Akcay, 2010; Van der Voordt et al , 2017; Günes and Olguntürk, 2020; Montero-Parejo et al , 2020) to study color preferences of various types of spaces. Although the human perception of colors affecting their emotions is best described by Birren’s color theory, the preference for a given color of space is best stipulated by the ecological valence theory developed by Palmer and Schloss (2010).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This may have an impact on color preferences as individuals develop their color preferences related to the appearances of spaces that they are accustomed to. The color preferences themselves do not suffice to predict the actual behavior of occupants vis-à-vis interior design colors; however, scholars include various demographic variables into the equation such as age, gender and ethnicity (Sable and Akcay, 2010; Van der Voordt et al , 2017; Günes and Olguntürk, 2020; Montero-Parejo et al , 2020) to study color preferences of various types of spaces. Although the human perception of colors affecting their emotions is best described by Birren’s color theory, the preference for a given color of space is best stipulated by the ecological valence theory developed by Palmer and Schloss (2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A systematic literature review shows that the studies of color preferences are characterized by the dominant research about developed countries (Mahnke, 1996; Taft, 1998; Van der Voordt et al , 2017; Ulusoy et al , 2020; Günes and Olguntürk, 2020; Montero-Parejo et al , 2020) and none about developing countries in the context of the Western Balkans. In addition, from the literature review, it can be concluded that there are research gaps concerning the analysis of the color preferences in the context of comparing gender color preferences of main types of interior spaces in the residential built environment, especially in a developing economy with a booming residential real estate sector (Kosovo Agency of Statistics, 2021), in which architects and designers are research hungry and in need of comprehensive research studies to synthesize their design projects offering their audience a fulfilling interior experience taking fully into account the gender perspective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By using photo-based questionnaires, the authors give recommendations for the forest road planning and simultaneously enhancing the protection and sustainability of the ecosystem [17]. By assessing visual impact of buildings on rural landscape, researchers draw special attention to the façade colour that affects optical integration of buildings into the landscape [18]. The paper by Montero-Parejo also drew the visual integrity (visual continuity, compatible contrast) as one of valuable aesthetic criterion for landscape assessment (18).…”
Section: Literature Reviewmentioning
confidence: 99%
“…By assessing visual impact of buildings on rural landscape, researchers draw special attention to the façade colour that affects optical integration of buildings into the landscape [18]. The paper by Montero-Parejo also drew the visual integrity (visual continuity, compatible contrast) as one of valuable aesthetic criterion for landscape assessment (18). Based on previous research analysis coherence, complexity, legibility and mystery indicators explain the most complex and intriguing aesthetical perception criteria [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In rural built environment studies, researchers have used color data to extract dominant colors, guiding environmental color control for regional construction (20). Subsequently, some researchers highlighted the considerable impact of color differences on the harmony of built environments, examining how diverse building facade colors interfere with human attention (21). However, there is a gap in understanding the mechanism of built environment color change applied in traditional villages.…”
Section: Introductionmentioning
confidence: 99%